Inovasi Paket Wisata dan Strategi Promosi Digital Berbasis Komunitas di Desa Wisata Donokerto, Sleman - Wahyu Indro Widodo; Profita Aznam, Azis Fitri Profita Aznam (Jurnal Abdimas Pariwisata, 2025)
Innovation of Tour Packages and Community-Based Digital Promotion Strategies in Donokerto Tourism Village, Sleman. Donokerto is an area that has excellent potential in the field of agro-tourism and culture, which is reflected in the existence of salak pondoh agricultural landscapes, traditional practices of making black turmeric-based herbal medicine, batik art and musical art. However, this potential has not been fully optimised as a competitive tourist attraction. This community service programme is designed to answer these problems through a participatory approach that emphasises innovation in the preparation of experiential tourism packages and community capacity building in digital promotion management. The implementation method includes training, workshops, and simulations of tour package design with an emphasis on the use of local narratives to strengthen the interpretative and educational value of the tourism experience. The results of the activities showed an increase in community competence in systematically developing tour packages and a better understanding of the use of digital platforms for promotion.